Research on the U-shaped relationship between marketization process and corporate capital structure: Evidence from Chinese listed companies - Junzhou Xu; Ling Zhang (PLoS ONE, 2025)
This paper explores the U-shaped relationship between marketization and corporate capital structure using panel data from Chinese listed firms (2012–2021). Applying fixed effects and nonlinear regressions, we find that as marketization increases, leverage first declines and then rises, confirming a robust U-shaped pattern. In early reforms, improved institutions reduce debt reliance; in advanced stages, enhanced capital markets facilitate debt access. Additionally, state-owned equity weakens this relationship, while fixed asset proportion strengthens it. The findings enrich capital structure theory under institutional transition and offer policy and strategic insights for emerging markets.